Relationship of tennis play to executive function in children and adolescents - Ishihara, T.; Sugasawa, S.; Matsuda, Y.; Mizuno, M. (European Journal of Sport Science, 2017)
This study evaluated the association between the frequency of tennis play and executive function in children and adolescents. One hundred and six junior tennis players (6-15 years old) participated in this study. Executive function, including inhibitory control, working memory, and cognitive flexibility were evaluated at rest. Females showed better inhibitory control and cognitive flexibility than males. In males, more frequent tennis play was associated with higher basic processing speed and inhibitory control after controlling for age, gender, body mass index (BMI), and tennis experience. More frequent tennis play was associated with better working memory in both males and females after controlling for age, gender, BMI, and tennis experience. Furthermore, longer tennis experience was related to better cognitive flexibility in males after controlling for age, gender, BMI, and frequency of tennis play. These findings suggest that tennis play is associated with the development of three foundational aspects of executive function (i.e. inhibitory control, working memory, cognitive flexibility). Especially, frequent participation in tennis play is related to better inhibitory control and working memory, while longer experience of tennis play is associated with better cognitive flexibility. Although development of inhibitory control and cognitive flexibility is slower in males than in females, the associations between tennis play and inhibitory control and cognitive flexibility appear to be larger in males than in females.